Analisis Pembentukan Harga Komoditas Cabai Rawit dan Bawang Merah Pada Tingkat Eceran di Kota Ambon - Natelda R Timisela; Yuliahwati E Salampessy; Yolanda M T N Apituley (Universitas Pattimura, 2020)
The distribution channel is one of the significant factors that influence the price formation of a commodity. This research intended to analyze several factors that affect the price formation of cayenne and shallot at the retail level in Ambon City. The data collected in this research were primary and secondary. The samples used in this research consisted of 30 respondents of each commodity (shallot and cayenne), and eight people from each marketing agency or distributors (wholesalers, distributors, and retailers). The collected data were analyzed by applying Multiple Linear Regression analysis. The result of the research depicted that factors that influenced the price formation of cayenne at the retail levels were transportation (X1), the packaging (X3), the difference between in supply and demand (X5), while that factors that influence the price formation of shallots at the retail levels were transportation (X1), the difference between in supply and demand (X5), production (X6), and substitution goods (X7). Keywords: cayenne, shallot, price, retail ABSTRAK Saluran distribusi merupakan salah satu faktor yang mempengaruhi pembentukan harga suatu komoditas. Penelitian bertujuan untuk menganalisis faktor-faktor mempengaruhi pembentukan harga cabai rawit dan bawang merah ditingkat eceran di Kota Ambon. Sampel penelitian adalah pengecer komoditi bawag merah dan cabe rawit berjumlah masing-masing 30 responden. Analisis data menggunakan analisis regresi linear berganda. Hasil penelitian menunjukkan bahwa faktor-faktor yang memengaruhi pembentukan harga cabai rawit di tingkat eceran adalah transportasi (X1), kemasan (X3) dan selisih pasokan dan permintaan (X5), sedangkan faktor-faktor yang mempengaruhi pembentukan harga bawang merah di tingkat eceran adalah transportasi (X1), selisih pasokan dan permintaan (X5), produksi (X6), dan barang substitusi (X7). Kata Kunci: bawang merah, cabai rawit, harga, eceran